The Relationship Between Aspects of Biology Learning Motivation with the Cognitive Learning Achievement of Biology at SMA Negeri 1 Karanganyar in Class Year of 2011/2012 - Esti Rahayu; Puguh Karyanto; Riezky Maya Probosari (BIO-PEDAGOGI, 2012)
This research is aimed to know causal relationship between  knowledge,accomplishment, stimulation, integrated regulation, identified regulation, introjected regulation, and external regulation  with  cognitive  learning achievement  of  biology  at SMA Negeri 1 Karanganyar in academic year 2011/2012 simultaneously. This was a correlational research and conducted upon high school student at SMA Negeri 1  Karanganyar  in academic year  of  2011/2012. The sample was taken among 115  samples of  student using  stratified random  sampling  technique.  Documentation technique was used to    uncover student’s cognitive learning achievement, while aspects of motivation was measured by using questionnaire. The obtained data was analysed using multiple regression analysis in SPSS 16.  The result showed that there was a  negative  correlation betweenaccomplishment and introjected regulation  with  cognitive  learning achievement of     biology at SMA Negeri 1 Karanganyar in academic year 2011/2012 simultaneously. But the others  such as knowledge, stimulation, integrated regulation, identified regulation, and external regulation  showed no correlation  with cognitive  learning achievement    biology of the students of SMA Negeri  1 Karanganyar  in academic year 2011/2012    simultaneously. Key Words:  aspects of learning  motivation,  cognitive learning achievement ofbiology, multiple regression analysis